Community participation for sustainability of rural water schemes: A case of Chamavita water schemes in Lushoto district - Mdendemi, Patience P. (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the requirements for the Degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University